Direct Clipping of Paraclinoid Aneurysm in Conjunction with Extradural Anterior Clinoidectomy: Technical Nuance and Functional Outcome - Tsunoda, Sho; Inoue, Tomohiro; Takeuchi, Naoko; Akabane, Atsuya; Saito, Nobuhito (Journal of Neurological Surgery Part B: Skull Base, 2021)
Objective Because of their anatomical features, treatment for paraclinoid aneurysms has remained to be challenging. Thus, the aim of this report is to prove the validity of our surgical method for unruptured paraclinoid aneurysms, together with surgical videos.Study Design Between August 2017 and November 2019, we were able to perform surgical clipping for 11 patients with unruptured paraclinoid aneurysm using a completely unified method. This study investigated the effect of surgery on multiple measures, including visual impairment, brain contusion, temporalis muscle atrophy, and multiple neurocognitive functions.Results Of the 67 unruptured aneurysms treated at our hospital, 17 were identified to be paraclinoid aneurysm, and 11 of them were treated by direct clipping using anterior clinoidectomy. Three were ophthalmic artery aneurysms, three were superior hypophyseal artery aneurysms, and five were anterior carotid wall aneurysms without branch projection. Only one patient had asymptomatic mild enlargement of the Marriott blind spots postoperatively. No brain contusion and temporalis muscle atrophy were observed in any cases. Only the Trail Making test (TMT) showed a significant worsening in the acute postoperative period: mean pre- and postoperative TMT scores were 59.1 ± 29.1 and 72.7 ± 37.3 for Part A (p = 0.018) and 80.5 ± 35.5 and 93.8 ± 39.9 for Part B (p = 0.030), respectively. However, it improved in the chronic phase.Conclusion We can conclude that our surgical method is safe and can be considered an acceptable treatment. Although surgical stress can cause temporary executive dysfunction shortly after surgery, this decline is temporary.
Keywords: paraclinoid aneurysm; anterior clinoidectomy; neurocognitive function; temporalis muscle